Perbandingan Hematologi Kuda Sandelwood Yand Dipelihara Secara Intensif Dan Ekstenstif Di Desa Soru Kecamatan Umbu Ratu Nggay Kabupaten Sumba Tengah - Cesario Saputra Umbu Ngarang; Yeremia Y Sitompul; Filphin A Amalo (Jurnal Veteriner Nusantara, 2022)
The Sandelwood horse is a genetic resource (SDG) of a local Indonesian horse family that was developed in the Province of East Nusa Tenggara (NTT) with its original geographic distribution area on the island of Sumba. Data on Sumba horses are still very limited, including data on blood hematology. Hematological data are usually used for various purposes such as to determine the health status of animals, to help establish a diagnosis, to determine the prognosis and to monitor response to therapy or disease progression. The sample used in this study was Sumba horse blood, male sex, age 5 to 7 years. The horses were grouped into two groups, namely 20 intensively reared horses and 20 extensively reared horses. Blood hematology examination using a hematology analyzer. Statistical calculations are calculated using the SPSS application. Based on the results of data analysis on the SPSS 16.0 application, there was no significant difference between the two groups because the P > 0.05.